Projektwissen spielend einfach managen mit der ProjectWorld : HMD best paper award 2015 /: HMD best paper award 2015. ([2016]) - Schacht, Silvia; Reindl, Anton; Morana, Stefan; Mädche, Alexander
No abstract available